Effective Mechanisms for Handling Code of Ethics Violations by Election Organizers - Laxamanahady, Moch. Syafrudin Dwi Sapto; Musthofa, Moh Ahza Ali; Laxamana, M. Herzegovin (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2024)
Elections are fundamental to democracy, allowing for a leader’s free and fair selection. Electoral justice is essential for upholding election integrity by enforcing ethical standards and ensuring the professionalism of election organizers, thereby maintaining public trust and democratic principles. This research examines mechanisms for addressing violations of the electoral code of ethics, covering processes from reporting and investigation to sanctioning and preventive measures. The study utilizes a legal research methodology, employing statute and conceptual approaches. Findings indicate that the DKPP (Dewan Kehormatan Penyelenggara Pemilu) faces several challenges, including its limited presence with an office only in the capital, sanctions that are not sufficiently deterrent, and a small membership of only seven individuals. To improve effectiveness, DKPP needs to enhance human resource training, leverage information technology for better reporting systems, and boost transparency. The establishment of Regional Examination Teams (TPD) has been introduced to accelerate the handling of ethical violations in regional areas. DKPP aims to uphold the integrity and credibility of election organizers, which is crucial for ensuring fair and democratic elections. Raising public awareness about the importance of the code of ethics is also vital to preventing future violations. Despite implementing sanctions such as warnings and suspensions, the effectiveness of these measures remains in question. Strengthening oversight bodies, legal reforms, community engagement, and inter-agency collaboration are necessary to enforce the code of ethics effectively.